The influence of leadership style, work environment and work discipline on the performance of Arjasari health center employees - Rizki Fathurrahman Septian; Palupi Permata Rahmi; Yoyo Sudaryo; Gurawan Dayona Ismail; Nunung Ayu Sofiati (Efi); Dadan Abdul Aziz (Jurnal Scientia, 2024)
This research aims to determine the simultaneous or partial influence of leadership style, work environment and work discipline variables on the performance of Arjasari Community Health Center employees. In this study, the samples were employees of the Arjasari Community Health Center with a sample size of 30 people. This research uses quantitative methods with a total sampling technique. And the data analysis tool uses the SPSS version 25.0 program. Based on the results of research at the Arjasari health center, it shows that leadership style, work environment and work discipline influence employee performance both partially and simultaneously with a determination coefficient test value (R₂) of 0.978 or 97.8% so it can be interpreted as 97.8% The performance of Arjasari Community Health Center employees (Y) can be explained by the variables leadership style (X₁), work environment (X₂), and work discipline (X₃)